A spatially specified systems pharmacology therapy for axonal recovery after injury - Mustafa M. Siddiq; Nicholas P. Johnson; Nicholas P. Johnson; Nicholas P. Johnson; Yana Zorina; Arjun Singh Yadaw; Carlos A. Toro; Carlos A. Toro; Jens Hansen; Vera Rabinovich; Sarah M. Gregorich; Yuguang Xiong; et al. (Frontiers Media S.A., 2023)
There are no known drugs or drug combinations that promote substantial central nervous system axonal regeneration after injury. We used systems pharmacology approaches to model pathways underlying axonal growth and identify a four-drug combination that regulates multiple subcellular processes in the cell body and axons using the optic nerve crush model in rats. We intravitreally injected agonists HU-210 (cannabinoid receptor-1) and IL-6 (interleukin 6 receptor) to stimulate retinal ganglion cells for axonal growth. We applied, in gel foam at the site of nerve injury, Taxol to stabilize growing microtubules, and activated protein C to clear the debris field since computational models predicted that this drug combination regulating two subcellular processes at the growth cone produces synergistic growth. Physiologically, drug treatment restored or preserved pattern electroretinograms and some of the animals had detectable visual evoked potentials in the brain and behavioral optokinetic responses. Morphology experiments show that the four-drug combination protects axons or promotes axonal regrowth to the optic chiasm and beyond. We conclude that spatially targeted drug treatment is therapeutically relevant and can restore limited functional recovery.